Population health management in health care organizations - McAlearney, Ann Scheck; Hefner, Jennifer L.; Huerta, Timothy R. (Advances in health care management ;, 2014)
The mission of healthcare organizations has undergone a remarkable transformation from curing disease to caring for the well-being of populations. While health care policy has explored this domain before, notably in Health Maintenance Organizations, the current efforts to create Patient-Centered Medical Homes (PCMHs) and Accountable Care Organizations (ACOs) represent a broader effort to move organizational responsibilities towards population health and care management. Volume 16 of AHCM presents papers that explore this topic across various levels of the healthcare system and employing multiple research designs including case studies, theoretical pieces, secondary data analyses, survey research and qualitative methodologies. Aspects of health care organization discussed in this volume include the PCMH, ACOs, integration with the public health and mental health systems, hospital-physician alignment, and resource planning. Population health management is presented as a factor driving these organizational changes and as a mechanism to facilitate this change.